A judge must not be influenced by fear. Must a judge be brave? : The duty of judges to defend judicial independence and the rule of law - Sunnqvist, Martin (Oñati Socio-Legal Series, 2025)
It is not acceptable that a judge because of ‘fear’ hands down a wrongful judgment. This was mentioned already by Isidore of Seville in his Sententiae and is part of the oaths of judges in many jurisdictions, from the 1230s onwards until this day. The ‘fear’ that is relevant could relate to one of the parties but also other persons in power. Thus, it relates not only to impartiality but - above all - to independence. Fear is often paired with favour, meaning that a judge should not try to please those in power through his judgments. In this paper I discuss whether the obligation of the judge not to be influenced by fear is only to be understood in the negative sense, or also in the positive - that is, does a judge have to be brave and, for example, oppose actions by persons in power that aim at undermining independence and impartiality? In other words, what are the ethical requirements when a judge perceives a risk that only avoiding being influenced by fear in individual cases will not be enough to protect independence and impartiality for the future?